IDENTIFICATION OF CHROMOSOME CONFORMATION SIGNATURES INVOLVED IN PROGRESSION OF TYPE-2 DIABETES MELLITUS USING EPISWITCH™ - P, Janisha; M, Tsu Horng; N, Serene; P, Yun Xin; K, Christina; H, Ewan; A, Hock Aun; L, Irene; T, Peng Yeow; MN, Juliana; G, Kurubaran; M, Delis Suzan; et al. (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Prevalence of Type-2 Diabetes Mellitus (T2DM) has increased more than 50% in 2006-2015 (National Health and Morbidity Survey, 2015). Oxford Biodynamics has demonstrated using Chromosome Conformation signatures (CCS) (Salter M. et al, 2018), as the most informative molecular entity in epigenetics for stratification of phenotypes. The proprietary EpiSwitch™ biomarker discovery platform is employed to find markers informative of T2DM progression. METHODOLOGY We have recruited a total of 409 subjects and categorised them into 4 groups, i.e. healthy, pre-diabetes, diabetes treatment naïve and treated diabetes; n=122, 90, 77, 120, respectively, based on glycated haemoglobin (HbA1C), fasting blood glucose (FBG) and oral glucose tolerant test. HbA1C, FBG and relevant clinical data of these subjects were followed up for 2 years at a 6-month interval. Five pre-diabetes, 6 diabetes treatment naïve and 6 treated diabetes samples were selected based on baseline data and compared against a pool of 16 healthy controls using proprietary microarray. RESULTS Follow-up blood tests showed 2 pre-diabetes samples progressed to diabetes. After comparing against samples regressing either from pre-diabetes to healthy, diabetes to pre-diabetes, diabetes to healthy and samples that are constantly diabetes, 59 unique progression markers have been identified. Functional analysis of the 59 markers using STRING database showed that the markers are significantly involved in T2DM and insulin resistance pathway; false discovery rate 1.87e-09 and 5.39e-09 respectively. CONCLUSION Four markers overlapped and interconnected between insulin resistance and T2DM pathways demonstrate the significance and robust outcome of the methodology. CCS of these markers can be used to stratify risk among healthy and pre-diabetes people. The developed blood-based testing not only provides unprecedented early solutions for management, diagnosis and treatment of T2DM but also promising clues on the mechanism of T2DM progression. A further validation with cohort collected is to follow.